Determinants of Medication Adherence and the Impact of Proactive Home Pharmacy Services in Rural South Sulawesi - Kamri, Andi Maulana; Ashar, Ainun Maharani; Azizah, Rizqi Nur (Sciences of Pharmacy, 2026)
Hypertension poses a considerable health challenge in Indonesia, particularly in South Sulawesi, marked by elevated rates of medication non-adherence. Pharmacist-led home intervention models may serve as effective strategies for engaging disadvantaged populations, especially in regions with restricted healthcare access. This study seeks to investigate determinants influencing medication adherence in hypertensive patients at Puskesmas Mandai, Maros Regency, to inform the development of a pharmacist-led home care intervention model. A cross-sectional study was conducted from February to September 2025 with 35 participants, predominantly elderly women with limited educational attainment. Data were gathered through standardized questionnaires and analyzed descriptively and inferentially, incorporating forest plot visualization for odds ratios (OR). Research findings identified two primary drivers of adherence: belief in medication (OR=2.45) and information provided by pharmacists (OR=2.14). Current conditions reveal significant deficiencies 77.14% of patients lack sufficient information from pharmacists, and 51.42% do not comprehend the quality of medications utilized. These findings signify the necessity for shifting pharmaceutical services from reactive paradigms (awaiting patient visits) to proactive models (initiating patient engagement), exemplified by pharmacist-led home care, to address educational deficits and foster sustainable patient confidence. Augmenting pharmacist-led education and fostering patient trust in medicine are viable strategies to enhance adherence. These findings underscore the necessity for tailored interventions, such as home pharmacy care, to bridge knowledge gaps and strengthen pharmacists' roles in chronic disease management. Further research with larger samples is recommended to corroborate these trends.